1993
DOI: 10.1111/j.1528-1157.1993.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Regional Cerebral Blood Flow in West Syndrome

Abstract: Focal cortical disturbances are frequent sequelae in West syndrome (WS) even though it is a generalized epileptic syndrome. Functional neuroimaging was used to determine whether focal perfusion abnormalities exist at WS onset and change during evolution. We studied regional cerebral blood flow (rCBF) at different stages of WS. Mean CBF (mCBF) and rCBF were measured using SPECT (single photon emission computed tomography) and 133Xe in 13 WS patients: at onset (20 cases), just after steroids (17 cases), and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 28 publications
(27 reference statements)
4
36
1
Order By: Relevance
“…Ictal SPECT had been used as a new method of slow dye infusion according to a previous study [9]. Regardless of the difficulty of ictal SPECT in IS, we experienced high concordance (71.4%) with EEG foci, and our findings are similar to the results of previous studies [9,19,20]. Also, localized cerebral hypoperfusion on interictal SPECT might often be associated with IS, even when the MRI is normal, while focal hypoactivity in SPECT could reflect a cortical lesion corresponding to the EEG foci [19,20,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…Ictal SPECT had been used as a new method of slow dye infusion according to a previous study [9]. Regardless of the difficulty of ictal SPECT in IS, we experienced high concordance (71.4%) with EEG foci, and our findings are similar to the results of previous studies [9,19,20]. Also, localized cerebral hypoperfusion on interictal SPECT might often be associated with IS, even when the MRI is normal, while focal hypoactivity in SPECT could reflect a cortical lesion corresponding to the EEG foci [19,20,21,22].…”
Section: Discussionsupporting
confidence: 82%
“…15,16 In adults, partial status epilepticus with reversible DWI images 4,17 involve the cortical region of seizure origin. ADC is decreased by 6 to 28% or increased by 46%.…”
Section: Discussionmentioning
confidence: 99%
“…Although spasms can be ascribed to a variety of etiologies (such as perinatal events, brain malformations, and genetic or chromosomal abnormalities), the clinical and electroencephalographic phenotypes are stereotypical - suggesting the involvement of highly specific, age-dependent processes that involve both cortical and subcortical structures (Lado and Moshé, 2002). In positron emission tomography (PET) and single-photon emission computed tomography (SPECT), hemodynamic and metabolic changes have been described within cortical malformations (Hrachovy and Frost, 1989, Chiron et al, 1993, Chugani et al, 1990, Haginoya et al, 2013), but also in remote cortical and subcortical structures, including the brainstem (Hrachovy and Frost, 1989, Chiron et al, 1993, Chugani et al, 1990, Chugani et al, 1992, Haginoya et al, 1998, Haginoya et al, 1999, Haginoya et al, 2013). Some authors suggested that the involvement of the cortex is restricted to the cortical malformations (i.e.…”
Section: Introductionmentioning
confidence: 99%